Avoiding politics : - Eliasoph, Nina (Cambridge University Press, 1998)
Civic groups are said to be the fount of democracy, but these vivid portraits of American life reveal an intriguing culture of political avoidance. Nina Eliasoph accompanied volunteers, activists and recreation club members, listening to them talk--and not talk--politics, in a range of private and public settings. Unlike interview-based studies of political participation and civic culture, Avoiding Politics shows how citizens create and communicate political ideas in everyday life, and the hard work it takes to produce apathy in a democracy